Penggunaan Desain Pembelajaran dalam Meningkatkan Keterampilan Membaca Siswa SD Kelas III SDN Curug 1 - Ina Magdalena; Tio Saputra; Sihury Wellya Pamungkas; Raihan Fadhlurahman Jamirullah (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2020)
This research was conducted at SDN Curug 1. The purpose of this study was to determine the use of learning designs in improving reading skills of third grade students. The object of this research is a class III teacher at SDN Curug 1. The method used in this research is qualitative research using observation, interview and documentation techniques. Class teachers at SDN Curug 1 use the design method of learning to read aloud and fast and the teacher also uses the existing library in the form of interesting reading books so that students are expected to be able to improve their reading skills.